2019
DOI: 10.4028/www.scientific.net/msf.967.228
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Na<sub>2</sub>SiO<sub>3</sub>/NaOH Ratios on the Volumetric Properties of Fly Ash Geopolymer Artificial Aggregates

Abstract: This study was conducted as a part of a research to assess the influence of the volumetric properties of geopolymer artificial aggregates made of fly ash to the performance of asphalt mixture to be used in pavement layers. This paper presents the parameters adopted during the production of geopolymer artificial aggregates which may affect the volumetric properties and the structure of the aggregates. The investigated volumetric properties included specific gravity and water absorption. In the experiment labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
4
0
3
Order By: Relevance
“…The denser matrix that is shown in Figure 5 for geopolymer aggregate with the solid-to-liquid (fly ash/alkaline activator) ratio of 3.0 results in a lower AIV value, where the strength of the geopolymer aggregate is higher. The geopolymer aggregates indicated that excellent solidification of the fly ash with alkaline activators occurred by geopolymerization reaction as the alkaline activator dissolved most of the fly ash particles [ 79 ]. Furthermore, the SEM of quarry tailings autoclaved aggregate in Figure 6 showed that high stream curing had a denser structure, which increased the strength alongside with reduced water absorption of the aggregate [ 37 ].…”
Section: Physical and Mechanical Properties Of Lightweight Aggregatementioning
confidence: 99%
“…The denser matrix that is shown in Figure 5 for geopolymer aggregate with the solid-to-liquid (fly ash/alkaline activator) ratio of 3.0 results in a lower AIV value, where the strength of the geopolymer aggregate is higher. The geopolymer aggregates indicated that excellent solidification of the fly ash with alkaline activators occurred by geopolymerization reaction as the alkaline activator dissolved most of the fly ash particles [ 79 ]. Furthermore, the SEM of quarry tailings autoclaved aggregate in Figure 6 showed that high stream curing had a denser structure, which increased the strength alongside with reduced water absorption of the aggregate [ 37 ].…”
Section: Physical and Mechanical Properties Of Lightweight Aggregatementioning
confidence: 99%
“…Penggunaan geopolimer sebagai agregat menunjukkan nilai absorpsi yang tinggi. Terendah sebesar 6,1% didapatkan pada rasio sodium silikat dan sodium hidroksida 2,5 (Karyawan et al, 2019).…”
Section: Pendahuluanunclassified
“…Rasio alkali yang sama, menghasilkan karakteristik mekanis dan mikrostruktur agregat geopolimer fly ash terbaik (Karyawan et al, 2020). Ide menggunakan tanah liat ini sebagai bahan yang direkomendasikan kepada tukang dan pengelola tempat penginapan, muncul berdasarkan hasil penelitian menggunakan lumpur Sidoarjo.…”
Section: Pendahuluanunclassified
“…The resistance to cracking of SMA can be increased by the use of RAP and SWP of up to 12% [1]. The application of fly ash as an artificial aggregate [2], [3], has the potential as a partial substitute for natural aggregate [4], with skid resistance that meets the requirements of roads in urban areas with traffic speeds below 95 km/hour [5]. Recently, the utilize of natural asphalt in the form of rock asphalt containing aggregates and asphalt was developed as a road pavement material.…”
Section: Introductionmentioning
confidence: 99%